Government Institution Collaboration In Efforts To Handling Criminal Acts Of Human Trafficking In Indonesia Case Study: Literature Study For The Area Of East Nusa Tenggara Province - Tunggal Bayu Laksono; Maidah Purwanti (Journal of Law and Border Protection, 2019)
Trafficking in persons is a criminal act of organized crime that occurs internationally. Indonesia, as one of the countries with the fourth largest population, has experienced this crime. One of the provinces that is the center of this biggest crime is East Nusa Tenggara. In this case, the Indonesian government through existing state institutions coordinates to eliminate the crime of trafficking in persons. Immigration as one of the agencies that deals with immigration traffic problems plays a major role in efforts to deal with the Crime of Trafficking in Persons. Coordination between one party and another is carried out by the provincial government of East Nusa Tenggara. However, improving coordination is a key point of success in handling the Crime of Trafficking in Persons. This research was conducted by conducting a literature case study which aims to find out more about the crime in question. This writing is done with a descriptive research method by describing the research results in a case study literature from various literatures used by the author.